Identification of responsible sequences which mutations cause maternal H19-ICR hypermethylation with Beckwith–Wiedemann syndrome-like overgrowth - Satoshi Hara; Fumikazu Matsuhisa; Shuji Kitajima; Hitomi Yatsuki; Musashi Kubiura-Ichimaru; Ken Higashimoto; Hidenobu Soejima (Communications Biology)
Abstract Beckwith-Wiedemann syndrome (BWS) is caused by a gain of methylation (GOM) at the imprinting control region within the Igf2-H19 domain on the maternal allele (H19-ICR GOM). Mutations in the binding sites of several transcription factors are involved in H19-ICR GOM and BWS. However, the responsible sequence(s) for H19-ICR GOM with BWS-like overgrowth has not been identified in mice. Here, we report that a mutation in the SOX-OCT binding site (SOBS) causes partial H19-ICR GOM, which does not extend beyond CTCF binding site 3 (CTS3). Moreover, simultaneously mutating both SOBS and CTS3 causes complete GOM of the entire H19-ICR, leading to the misexpression of the imprinted genes, and frequent BWS-like overgrowth. In addition, CTS3 is critical for CTCF/cohesin-mediated chromatin conformation. These results indicate that SOBS and CTS3 are the sequences in which mutations cause H19-ICR GOM leading to BWS-like overgrowth and are essential for maintaining the unmethylated state of maternal H19-ICR.